Evaluation of lymphocytic infiltration in the bronchial glands of Sjögren’s syndrome in transbronchial lung cryobiopsy - Okabayashi, Hiroko (BMC Pulm Med, 2020)
BACKGROUND: Sjögren’s syndrome (SS) is a systemic autoimmune disease characterized by deteriorated exocrine gland function with associated lymphocytic infiltration. However, there are few pathological studies on bronchial glands in SS. In this study, we aimed to clarify pathological features of bronchial glands in SS. METHODS: We retrospectively evaluated infiltration of lymphocytes in the bronchial glands incidentally collected by transbronchial lung cryobiopsy (TBLC), which were performed for the diagnosis of diffuse lung diseases. The degrees of lymphocyte infiltration in the bronchial glands were classified into four grades (grade 0–3). We compared the degrees of infiltration of SS with those of other diffuse lung diseases. RESULTS: TBLC for diagnosis of diffuse lung diseases were performed on 432 cases during the study period. The samples of 50 cases included bronchial glands. Of those, 20 cases were excluded due to insufficient size or influence of therapy. The remaining 30 cases included 17 of idiopathic interstitial pneumonias, 5 of chronic hypersensitivity pneumonia, 6 of connective tissue disease (SS; n = 4, systemic sclerosis; n = 1, dermatomyositis; n = 1) and 2 of other diseases. In SS, infiltration of lymphocytes was observed in all cases; grade 1 in one, grade 2 in one, and grade 3 in two cases. In contrast, 11 of 26 in other diseases showed no lymphocytes infiltration, with the remaining 15 of grade 1 infiltration. Grade 2 or more infiltration were found only in SS but not in other diseases. CONCLUSION: Our results suggested that high-grade lymphocytic infiltration of bronchial glands is a distinct characteristics in SS.